ANALYSIS OF SOIL QUALITY BIOINDICATORS IN GRAIN CULTIVATION SYSTEMS (SOYBEAN AND CORN) IN THE REGION OF SANTARÉM, MOJUÍ DOS CAMPOS AND BELTERRA, PA (International Seven Journal of Multidisciplinary, 2025)
The aim of this work was to analyze the biological indicators of the soil in areas where grain, soy and corn are grown in the region of Santarém, Mojuí dos Campos and Belterra Pará. The analyses were carried out using BioAS technology, developed by EMBRAPA Cerrado. Through enzyme activity, it is possible to access the soil memory associated with the non-living fraction accumulated in the protected soil, through absorption in clay particles and organic matter. Soil samples were collected from four areas: Tapajós National Forest - FLONA (very clayey texture), Novo Horizonte Farm (very clayey texture) and two areas on Texa Farm (clayey and medium clayey texture). Samples were collected at depths of 0 to 10 and 10 to 20 cm at the end of the region's rainy season. The samples were packaged, identified and sent to the EMBRAPA Amazônia Oriental Laboratory in Belém, where enzymatic analyses of arylsulfatase and β-glucosidase were carried out. The data obtained was subjected to descriptive statistics, analysis of variance (p